Familiarization Field Trip to CCARDESA GCCA + Project in Katapazi Camp, Mungala Village under Chief Mukuni of Southern Province, Zambia - Magagula, Futhi; Mungambata, Sunga (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The purpose of the familiarization tour was to interact with the farmers who are implementing a community led solar powered irrigation scheme and appreciate what the CCARDESA project is implementing and the existing conditions and facilities available in Katapazi agricultural camp. The report also aims to document the findings, observations, and recommendations related to the implementation and impact of drip irrigation on crop yield, water conservation, and farmer livelihoods.